Jejak Hijau TOGA Mahasiswa KKN Uniwara di Tanah Desa Kemantrenrejo, Kabupaten Pasuruan - Zakiyah, Kuni; Dermawan, Akbar Satria; Farosanti, Lafnidita; Ula, Wardah Febrianas; Hidayah, Nilna Bariroh (CV Litera Inti Aksara, 2025)
The TOGA Green Trail program conducted by students from the 10th Community Service Program (KKN) of PGRI Wiranegara University (Uniwara) in Kemantrenrejo Village, Rejoso District, Pasuruan Regency, aims to revive the tradition of using herbal plants to support health while creating productive green spaces. The implementation method involves several stages: field observation to determine strategic locations, land clearing, preparation of planting media consisting of soil and rice husk ash, planting of family medicinal plant seedlings, landscaping with fencing and decorations, and technical guidance on plant care provided to the Head of Neighborhood Association (RW) 02 as a community representative. The results demonstrate the creation of a TOGA garden that is not only ecologically and health-beneficial but also has the potential to provide economic value and leave a lasting contribution to the village community even after the KKN program has concluded.